Integration, Innovation, and Empowerment: Exploring Teaching Reform Paths for Engineering Thermodynamics in the “Dual Carbon” Era - Zhang, Yang; Zhu, Shengnan; Zheng, Yaping; Tao, Hongge; Chen, Binglin; Xu, Guizhuan (Journal of Research in Vocational Education, 2026)
Against the backdrop of the global energy transition and technological revolution intertwined in the “Dual Carbon” era, the traditional Engineering Thermodynamics course faces multiple challenges such as outdated content, monotonous teaching models, and a disconnect between theory and engineering practice. Based on teaching reform practices from several leading universities, this paper systematically analyzes the core demands of the new era for talent cultivation in this field. It constructs a systematic path for teaching reform from four dimensions: “modernization of content and value guidance,” “intelligent and adaptive teaching modes,” “project-based and challenge-driven teaching methods,” and “collaborative and fully-integrated practical systems.” Research indicates that by deeply integrating cutting-edge technologies like artificial intelligence, building virtual-physical combined practice platforms, and implementing teaching models oriented toward authentic, complex engineering problems, students’ intrinsic motivation can be effectively stimulated. This cultivates their innovative thinking and practical ability to solve frontier energy science and engineering challenges, providing high-quality talent reserves to support the national energy strategic transition. The paper further explores the synergistic effects of these multidimensional reforms and their replicability, offering a comprehensive framework and actionable insights for the transformation of engineering foundational courses in the new era.